(3GdbhGYO GdNGUI HGdJhbjY GdEdcJQhfj (B=s The special rules of electronic signature - (3QHVj, YjSi ZSGfs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2012)
(3Ydi GdQZe ef GdJbOe GdYdej GdeJJGdj GdPj TgOg GdEfSGf Ydi eQ GdReGf, EdG Cf QMe GdMjGI GdYdejI(B-(3MJi hbJfG GdMGVQ(B-(3dG RGd jOaY ef Mjf dBNQ HehdO GdLOjO GdPj jMed ef GdeejRGJ hGdUaGJ GdJj de Jcf ehLhOI aj SGHbg, aGdMjGI GdYdejI dG RGdJ aj eQMdI GdeNGV de JJMOO eYGdegG HYO(B. (3hJYO KhQI GdeYdheGJ GdJcfhdhLjI hGdJbfjI GdJj jTgOgG YGdefG(B-(3hGdJj CUHMJ YfhGf gPG GdYUQ(B-(3GdehdhO GdLOjO GdPj OaYg dfG QMe GdMjGI GdYdejI, aHYO Cf fLM GdEfSGf aj UfY BdI JfhH Yfg YVdjG, SYi dHfGA BdI JNaa Yfg PgfjG, hbO JcddJ eSGYjg aj ENQGL GdMGSH GdEdcJQhfj GdQbej, heY JYGXe LghOg aj JWhjQ gPG GdCNjQ hEONGdg aj EHQGe GdJYGbOGJ, MOKJ fbdI fhYjI aj GdhSjdI GdeSJNOeI aj EHQGe GdJYGbOGJ(B. (3abO cGf dJWhQ eLGd JcfhdhLjG GdeYdheGJ hbWGY GdGJUGdGJ GdPj jeQ Hg GdYGde aj GdhbJ GdQGgf, CKQg GdHGdZ hGdhGVM Ydi GdeHGOF GdQGSNI aj GdacQ GdbGfhfj, NGUI YfGUQ Odjd GdEKHGJ (B((3GdcJGHI hGdJhbjY(B) (3GdJj Jbhe Ydi hSW eGOj eMShS hedehS, abO UGMH gPG GdJWhQ XghQ CfeGW hCTcGd eJYOOI ddhSGFd GdJj jJe ef NdGdgG EHQGe GdJUQaGJ GdbGfhfjI, aHjfeG cGfJ gPg GdJUQaGJ JfTC HhGSWI GdcJGHI GdJbdjOjI (B((3GdNWjI(B) (3hJhbY HhGSWI CMO CTcGd GdJhbjY GdJbdjOj Ydi hSjW eGOj eMShS, CUHMJ GdBf JfTC HhGSWI JbfjGJ MOjKI JJCda ef cJGHI EdcJQhfjI; hJhbY EdcJQhfjG Ydi hSjW ZjQ eGOj hZjQ eMShS, hbO CSge GdGfOeGL GdPj MUd Hjf GdKGdhK (B: (3GdMGSH GdEdcJQhfj, eLGd JcfhdhLjG GdeYdheGJ, hbWGY GdGJUGdGJ(B-(3hGdPj CaQR THcI GdGJUGdGJ GdMOjK`I (B"(3GdEfJQfJ(B"-(3aj RjGOI GSJNOGe GdJbfjGJ GdMOjKI aj EHQGe GdJUQaGJ GdbGfhfjI, abO CUHMJ gPg GdTHcI fGaPI GdEfSGf Ydi YGdeg jeGQS ef NdGdgG `` hYf HYO `` eYXe fTGWGJg hJUQaGJg Ohf JQMGd, EP HhGSWJgG cSQ MhGLR GdecGf hGdReGf, agj JUd CWQGa GdeYehQI aj KhGf eYOhOI, Hd aj CLRGA ef GdKGfjI aj HYV GdCMjGf, hgPG eG jYQa HGdJLGQI GdEdcJQhfjI(B. s
(3HHdjhLQGajI (B: (3UaMI (B287-302.s
Keywords: (3GdJhbjYGJ GdQbejIs -- (3bhGfjf hJTQjYGJs; (3GdJLGQI GdEdcJQhfjIs -- (3bhGfjf hJTQjYGJs